Once there was a house, a house that was a-- home - Smith, Alex T. (Tiger Tales, 2010)
Four best friends share a home until each wants to live in a different location. They can't agree on where to go, so they go their separate ways, each taking a part of the house with them. What will bring the four not-so-best friends and their home back together?